PENGARUH KEPATUHAN KONSUMSI SUPLEMEN ZAT BESI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PIYUNGAN - Fadhiyatul Khoiriah; Sylvi Wafda Nur Amellia; Widy Nurwiandani; Mahindria Vici Virahaju (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Bleeding during childbirth and the postpartum period is partly caused by anemia during pregnancy. According to the World Health Organization (WHO), approximately 40% of maternal mortality rates in developing countries are related to anemia during pregnancy. One of the causes of anemia in pregnant women is non-compliance with ron supplement consumption. Compliance with iron tablet consumption by pregnant women can ensure an increase in hemoglobin levels. The purpose of this study was to determine the effect of compliance with iron supplement consumption on the incidence of anemia in pregnant women at the Piyungan Community Health Center. The research method used was a quantitative experimental design. The design used in this study is a pre-experimental design with a one-group pretest-posttest design. The study population consists of all pregnant women who underwent examinations at the Piyungan Health Center, totaling 668 pregnant women. The sampling technique used is purposive sampling. Data analysis was performed using the Wilcoxon Signed Rank Test. The results of the study indicate that there is an association between compliance with iron supplement consumption and the incidence of anemia in pregnant women, as evidenced by the asymptotic significance value of p = 0.000. Health centers are encouraged to continue implementing iron supplementation programs as part of routine antenatal care and ensure that pregnant women regularly consume iron supplements, with a minimum of 90 tablets during pregnancy. Additionally, educational programs should be enhanced to emphasize the importance of iron supplements in improving compliance among pregnant women as a preventive measure against anemia.